Economics and the future time and discounting in private and public decision making - Pannell, David J., 1960-; Schilizzi, Steven; Edward Elgar Publishing (Cheltenham [England] : Edward Elgar Pub., 2006)
Economics and the Future tackles the discounting issue from a number of angles, ranging from relatively short-term private financial decisions, to very long-term public issues spanning generations. The authors present differing perspectives and original ideas in a style that remains accessible while addressing some of the more difficult questions about discounting in theory and practice. It reveals that the economic issues regarding time are embedded in a broader social, ethical and philosophical context.
1. Time and discounting in economic decision making / David J. Pannell and Steven G.M. Schilizzi -- 2. Investigating net benefits from alternative uses of resources / Bill Malcolm -- 3. Avoiding simplistic assumptions in discounting cash flows for private decisions / David J. Pannell -- 4. Compounding and discounting under risk : net present values and real option values / Greg Hertzler -- 5. Risk, discounting and the public sector / John Quiggin -- 6. Reconsidering reconsidered : why sustainable discounting need not be inconsistent over time / John C.V. Pezzey -- 7. Discounting the distant future using short time horizons : investments with irreversible benefits / Steven G.M. Schilizzi -- 8. Discounting future prospects, and the quest for sustainability / Alan Randall -- 9. How should we discount the future? : an environmental perspective / Michael D. Young and Darla Hatton MacDonald -- 10. Discounting the future / Cédric Philibert -- 11. Discounting the distant future : why so many voices and so little consensus? / Steven G.M. Schilizzi -- 12. Time will tell : pending questions on discounting / Steven G.M. Schilizzi and David J. Pannell.
Includes bibliographical references and index.
Keywords: Cost effectiveness; Decision making; Electronic books